Bacteria−Based Synergistic Therapy in the Backdrop of Synthetic Biology - Bao, Yawei; Cheng, Yong; Liu, Wei; Luo, Wenguang; Zhou, Peijie; Qian, Dong (Frontiers in Oncology, 2022)
Although the synergistic effect of traditional therapies combined with tumor targeting or immunotherapy can significantly reduce mortality, cancer remains the leading cause of disease related death to date. Limited clinical response rate, drug resistance and off-target effects, to a large extent, impede the ceilings of clinical efficiency. To get out of dilemmas above, bacterial therapy with a history of more than 150 years regained great concern in recent years. The rise of biological engineering and chemical modification strategies are able to optimize tumor bacterial therapy in highest measure, and meanwhile avoid its inherent drawbacks toward clinical application such as bacteriotoxic effects, weak controllability and low security. Here, we give an overview of recent studies with regard to bacteria-mediated therapies combined with chemotherapy, radiotherapy and immunotherapy. And more than that, we review the bacterial detoxification and targeting strategies via biological reprogramming or chemical modification, as well as their applications and clinical transformation prospects.